PERHITUNGAN BURN UP SECARA SEMI ANALITIK DAN NUMERIK PADA RANTAI TRANSMUTASI KOMPLEKS - Rif&rsquo (Matematika dan Sains, 2011)
Performance of the reactor core influence by changes the composition of nuclear material, including the neutron distribution and power. Therefore it is important to monitor the isotropic composition in the core during reactor operation, because some of fission product may affect the performance of the reactors. Burn up calculation performed in this study using Bateman equations as semi-analytic approach and explicit finite difference as numerical approach. The calculation of burn-up is done every day and alternating with the calculation of diffusion of each one year. Keff value for semi-analytical approach and numerical approach around of 1.00. This value has shown that reactor core on critics situation. The advantage of semi-analysis approach is able to calculate the nuclide has a short decay time and low disintegration constants than numerical approach, especially for transmutations chains complex. It means a semi analytical approach quite effectively applied in the burn-up calculation.eff value for semi-analytical approach and numerical approach around of 1.00. This value has shown that reactor core on critics situation. The advantage of semi-analysis approach is able to calculate the nuclide has a short decay time and low disintegration constants than numerical approach, especially for transmutations chains complex. It means a semi analytical approach quite effectively applied in the burn-up calculation.